Application of Serial Image Media to Improve Writing Skills in Indonesian Language Learning for Class 2 MI Az Zuhriyah Tanjung Students - Arfini, Baiq Desy; Nurlaila, Nurlaila (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was conducted to examine whether the application of serial image media can improve writing skills in Indonesian language learning for grade 2 students at MI Az Zuhriyah NW Tanjung. The research methods used are quantitative and qualitative, where the type of research used is Classroom Action Research (PTK). namely a cycle consisting of activities: planning, action, observation and reflection. The data is collected through process assessment and assessment of the results at the end of each action. In the end, the results of this classroom action research show that through Image Media the writing ability of class Ⅱ MI Az Zuhriyah NW Tanjung students can be improved. The results of this research, which was carried out using the method of applying serial image media, can improve children's writing skills. The improvement in writing skills in class II children at MI Azzuhriyah NW Tanjung can be seen in each cycle, both from cycle 1 and cycle II. Children's writing development increased from the pre-cycle category by 0.13% to 0.2% in cycle 1 of the first meeting and 0.26% in the second meeting. In cycle 1, if the criteria were not reached, it was continued in the second cycle until it reached 94.32%.